2020
DOI: 10.3389/fpubh.2020.579071
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Seatbelt Use Among Saudi Adults: Results From the National Biobank Project

Abstract: Introduction: Road traffic crashes (RTCs) are a leading cause of death and disabilities and impose a significant burden on the healthcare system and economy of Saudi Arabia. Around 20% of all hospital beds are occupied by victims of RTCs, which represent approximately 80% of trauma deaths occurring in these facilities. Using a seatbelt is an effective method to reduce traffic deaths and minimize the extent of associated injuries. However, little is currently known about the prevalence and predictors of seatbel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Various studies have reported numerous different results. The low seat belt compliance here is consistent with two previous studies that reported the overall rate of seat belt use as 27.85% and 34%, respectively (Alghnam et al, [ 5 , 15 ]). In comparison to that, a study that was conducted in Italy reported 51.8% use of seat belts [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Various studies have reported numerous different results. The low seat belt compliance here is consistent with two previous studies that reported the overall rate of seat belt use as 27.85% and 34%, respectively (Alghnam et al, [ 5 , 15 ]). In comparison to that, a study that was conducted in Italy reported 51.8% use of seat belts [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among the various factors that can lead to fatal RTAs, failing to use seat belts is considered significantly to be one of those risk factors [ 5 ]. A seat belt is defined as a safety strap designed in vehicles, which is used as a method of protection to sustain drivers and passengers during rides.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the percentage of adolescents who reported not wearing seat belts increased with age [ 17 ]. In another study, when other covariates were taken into account, those between the ages of 26 and 45 were 49% more likely to use a seatbelt than those between the ages of 18 and 25 [ 18 ]. Also, it was mentioned that more educated individuals are more likely to use seatbelts and understand their importance [ 19 ].…”
Section: Discussionmentioning
confidence: 99%